Shelf‐life extension of pomegranate arils using chitosan nanoparticles loaded with Satureja hortensis essential oil. (24th December 2020) - Amiri, Azam; Ramezanian, Asghar; Mortazavi, Seyed Mohammad Hassan; Hosseini, Seyed Mohammad Hashem; Yahia, Elhadi
Abstract: BACKGROUND: This study was conducted in two parts to improve the antimicrobial activity and stability of Satureja hortensis essential oil (SEO) and its impacts on the quality of pomegranate arils. In the first part, SEO was encapsulated by an ionic gelation technique into 142.2–267.7 nm chitosan nanoparticles (CSNPs). In the second part of the experiment, the CSNPs and CSNPs‐SEO were applied to improve storability of pomegranate arils. Arils were dipped in water (control), CSNPs and CSNPs‐SEO for 5 min. After superficial water removal, arils were packed into polystyrene boxes and stored at 5 °C for 18 days. RESULTS: Based on spectrophotometry analysis, the encapsulation efficiency (EE) of SEO‐loaded CSNPs (CSNPs‐SEO) decreased from 26.57% to 7.41% and their loading capacity (LC) increased from 4.72% to 6.17%, respectively, upon increasing the initial SEO content from 0.125 to 0.5 g g −1 of chitosan. Phytochemicals and water content were maintained, and microbial counts were reduced in the coated arils during storage. Total phenol and antioxidant activity decreased during storage. At the end of storage, the highest total phenol content (2980.0 mg gallic acid equivalents L −1 ) was found in arils treated with CSNPs‐SEO, whereas ascorbic acid content was maximal (6.32 mg L −1 ) in arils treated with CSNPs. The encapsulation of savory essential oil in chitosan nanoparticles did not have undesirable effects in pomegranate arils. CONCLUSION: Pre‐storage treatment of pomegranate arils with CSNPs‐SEO could be considered a beneficial treatment to better maintain the biochemical and sensorial quality during storage. © 2020 Society of Chemical Industry